The Culture of ListeningFrom the Rupestrian Pictures to the Audiocasts - Menezes, José Eugenio (Folios, revista de la Facultad de Comunicaciones y Filología, 2013)
Considering the diagnostic of the eyes’ distress, the necessity for reducing the spatial eye’s fixation and the enforcement in the ear’s capacities, which were all observed by Dietmar Kamper (1928-2001), this paper presents a bibliographical review and also raises questions born from the studies about the listening culture. In dialogue with Kamper, Baitello, Berendt, Plessner, Flusser and Bauer, this article features some possibilities of cultivation of communicative links in the context of the listening culture. From the silent contemplation of the rupestrian pictures from Serra da Capivara National Park (Brazil) and the hearing of the sonorous landscapes edited by Roberto D’Ugo, in audiocast format, this paper comprehends the relevance of the sonorous links in an increase of the bonding experiences and the citizenship.